AutoCAD 2011 and AutoCAD LT 2011 Bible. - Finkelstein, Ellen (Bible., 2010)
In-depth coverage of all new software features of AutoCAD and AutoCAD LT. AutoCAD is the leading drawing software, used by design and drafting professionals to create 2D and 3D technical drawings. This popular reference-tutorial has once again been revised by AutoCAD guru Ellen Finkelstein to provide you with the most up-to-date coverage of both AutoCAD and AutoCAD LT. You'll begin with a Quick Start tutorial so that even if you're brand new to AutoCAD, you can get started working with it right away. You'll then move on to the basics of creating drawings, using commands, and specifying coordin.